Tipe Partisipasi Masyarakat dalam Kegiatan Desa Wisata Nepal Van Java di Dusun Butuh Kecamatan Kaliangkrik Kabupaten Magelang - Janarko, Arya Dwi; Murdiyanto, Eko (Journal of Agricultural Social and Business, 2025)
This research aims to (1) Assess the type of community participation in the activities of the Nepal Van Java Tourism Village. This research is qualitative research with a case study method, using primary and secondary data sources, with data collection techniques through interviews, observation, documentation, then data validity with source triangulation. Data analysis techniques by collecting data, reducing data, presenting data and drawing conclusions. The results showed that (1)he types of community participation in Nepal Van Java tourism village activities include passive / manipulative participation, participation in providing information, consultation participation, material incentive participation, interactive participation, and selfmobilization.